2007
DOI: 10.3952/lithjphys.47319
|View full text |Cite
|
Sign up to set email alerts
|

Optical investigation and application of copper selenide nanowires

Abstract: Growth and optical properties of copper selenide nanowires (nws) in alumina template were studied and discussed in respect to their application as films doped with semiconductor nanocrystals that provide promising optical properties. The results obtained indicate that nanoscaled copper selenide structures uniformly embedded at the bottom of alumina less than a micron in depth could be useful for mode locking in picosecond YAG type lasers. The operating wavelength of the material was identified by optical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…In any case, the applied annealing conditions, lead to the formation of the orthorhombic crystal structure Cu 2 Se x and the cubic crystal structure Cu 1.8 Se. This result is in agreement with a previous study by R. Subas et al, at which no substantial improvement of the crystal structure was found at such high temperatures [26]. It is important to investigate lower annealing temperatures, around 300 °C, in order to achieve a higher contribution of β-phase Cu 2 Se to the final material.…”
Section: Modification Of Crystal Structure By Annealingsupporting
confidence: 92%
See 1 more Smart Citation
“…In any case, the applied annealing conditions, lead to the formation of the orthorhombic crystal structure Cu 2 Se x and the cubic crystal structure Cu 1.8 Se. This result is in agreement with a previous study by R. Subas et al, at which no substantial improvement of the crystal structure was found at such high temperatures [26]. It is important to investigate lower annealing temperatures, around 300 °C, in order to achieve a higher contribution of β-phase Cu 2 Se to the final material.…”
Section: Modification Of Crystal Structure By Annealingsupporting
confidence: 92%
“…Typically, annealing, in addition to improving the crystallinity of a material, [25] can be used to obtain different regions of the phase diagram. In particular, β-phase Cu 2 Se can be attained by using rapid cooling after annealing under appropriate conditions [26]. Previous studies have identified the use of annealing in pure or doped Cu-Se system to provide the Cu 2 Se cubic crystal structure i.e.…”
Section: Modification Of Crystal Structure By Annealingmentioning
confidence: 99%
“…It is obvious from the steady-state absorption spectra that variations of the electrodeposition parameters and post-deposition treatment result in distinct optical properties of each sample. It was demonstrated that the peak intensity of the absorption band related to the middle-gap states depends on the degree of the sample oxidation [20] and its energetic position can be tuned within the spectral range of 0.8-1.25 eV [14,21]. The sample annealing causes the most notable post-formation treatment effects.…”
Section: Resultsmentioning
confidence: 99%
“…Copper selenide is a precursor material of CuInSe 2 , used for highly efficient photovoltaic elements [5,12]. Attempts of application of copper selenide for optical filters [13], saturable absorbers for a passive mode locking of near-IR solid-state lasers [14], humidity sensors [15], highly effective hole injection layers for use with p-type organic semiconductors [3], novel nanotubes [16] have also been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años las nanoestructuras de seleniuro de cobre han tenido un alto interés dado que el seleniuro de cobre posee propiedades fascinantes y por ello amplias aplicaciones en campo tecnológico como: convertidores termoeléctricos 1 , filtros ópticos 2 , dispositivos fotoelectrónicos de alta eficiencia 3 , superconductores iónicos 4 , sensores de gases 5 , células solares 6 y fotocatalizadores 7 que permiten degradar productos químicos peligrosos. Es por eso que se vienen utilizando e implementando métodos para su síntesis como el solvotermal 8 , irradiación gamma 9 , sonoquímico 10 , electrodeposición 11 , evaporación al vacío 12 , coloidal 13 , deposición de baño químico 14 , deposición química de vapor 15 y deposición por láser pulsado 16 .…”
Section: Introductionunclassified